2001
DOI: 10.1177/14703203010020010801
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of responses to angiotensin II in the mouse

Abstract: Responses to angiotensin II (Ang II) were investigated in anaesthetised CD1 mice. Injections of Ang II caused dose-related increases in systemic arterial pressure that were antagonised by candesartan. Responses to Ang II were not altered by PD 123319. At the lowest dose studied (20 µg/kg i.v.), the inhibitory effects of candesartan were competitive, whereas at the highest dose (100 µg/kg i.v.), the dose-response curve for Ang II was shifted to the right in a non-parallel manner. The inhibitory effects of cande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…This chemical was chosen as a simple and effective agent for generating cellular oxidative stress levels without concomitant tissue injury. To date, there has not been a suitable alternative for an in vivo oxidative stress model without tissue injury (1,3,6,8,12,29,32,38). As reported in previous studies (2, 4) using PQ to generate high-level ROS to mimic disease systems, we observed a significant increase in oxidative stress markers in cardiac tissue within hours of treatment.…”
Section: Discussionsupporting
confidence: 77%
“…This chemical was chosen as a simple and effective agent for generating cellular oxidative stress levels without concomitant tissue injury. To date, there has not been a suitable alternative for an in vivo oxidative stress model without tissue injury (1,3,6,8,12,29,32,38). As reported in previous studies (2, 4) using PQ to generate high-level ROS to mimic disease systems, we observed a significant increase in oxidative stress markers in cardiac tissue within hours of treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Most transgenic mouse studies using AT 1a , AT 1b , and AT 2 receptor knockout animals showed that AT 1a R is the receptor that drives most physiological responses to angiotensin II including blood pressure control, 48 , 49 although other studies underscored the tissue‐specific roles of AT 1b R. 50 The lack of hypertension in VEC specific AT 1a R knock out mice 51 , 52 is somewhat conflicting with our results which can be explained by the more pronounced role of this vasodilator mechanism in stressed disease conditions compared with healthy conditions. Angiotensin II–induced VEC calcium responses were exclusively mediated via the AT 1 R, in agreement with earlier studies showing that acute vasoconstrictor responses to angiotensin II were mediated by actions at the AT 1 R, and that acute responses are not counterbalanced by opposing effects on the AT 2 R. 53 Other studies provided additional confirmation regarding the key role of the AT 1 R and that the AT 2 R does not contribute significantly to the observed angiotensin II–induced VEC calcium elevations or other vascular responses 54 , 55 including in brain microvessels. 56 Our results are also in agreement with the previous demonstration of AT 1 R‐mediated activation of VEC calcium signaling and NO production by angiotensin II, 18 , 19 which has been previously attributed to AT 2 R functions.…”
Section: Discussionsupporting
confidence: 91%
“…First, the present study exhibited the increment of MAP and RVR as well as the decrement of RBF in response to the infusion of Ang II in all groups receiving vehicle or A779. Te literature has documented the dose-dependent pressor responses to Ang II [12][13][14]. Ang II, as one of the most important peptides of RAS, elicits vasoconstrictor efects mediated by AT1R [2].…”
Section: Discussionmentioning
confidence: 99%